Immune dysfunction during S. aureus biofilm-associated implant infections: opportunities for novel therapeutic strategies - Nichole D. Brandquist; Tammy Kielian (npj Biofilms and Microbiomes)
Abstract Staphylococcus aureus is a common cause of biofilm infections, particularly on implanted medical devices. Biofilms are heterogeneous bacterial communities contained in a self-produced matrix that are poorly cleared by the immune system. This review discusses mechanisms employed by the biofilm, such as alterations in bacterial metabolism and toxin production, to induce immune dysfunction by highlighting recent bacterial single-cell sequencing studies. Additionally, the role of immune recognition and metabolism in biofilm containment is examined with an emphasis on the role of granulocytic myeloid-derived suppressor cells and how responses are tailored to distinct tissue niches. We also address emerging evidence revealing the importance of the infection microenvironment, host genetic variability, and bacterial heterogeneity in shaping immune responses during S. aureus biofilm infections.